Adsorption of Alcohols from Multicomponent Solutions onto Silica Gel - J. Goworek (Adsorption Science & Technology)
Adsorption equilibria of the binary and ternary solutions of alcohols in benzene and n -heptane on silica gel have been studied in order to clarify their mechanisms of adsorption. Excess adsorption isotherms have been measured for hydrocarbon solutions of methanol, ethanol, butanol and pentanol. Interpretation of the experimental data was performed in terms of material balance between bulk and surface phase. In n -heptane solutions the multilayer surface structure is formed and the surface phase contains the alcohol only. For benzene and ternary (alcohol + benzene + n -heptane) solutions a mixed surface phase is observed whose composition is determined by competition of liquid components for silica surface as well as its tendency to complex. Moreover, the extent of adsorption in methanol systems is connected with the miscibility of liquid components.